2004
DOI: 10.1128/jcm.42.6.2476-2479.2004
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Quantitative and Semiquantitative Enzyme-Linked Immunosorbent Assays for Immunoglobulin G against Chlamydophila pneumoniae to a Microimmunofluorescence Test for Use with Patients with Respiratory Tract Infections

Abstract: We previously reported a high degree of variation in the sensitivities of serodiagnostic kits for the detection of Chlamydophila pneumoniae in sera from healthy donors. Since a low predictive value of a test can impair its diagnostic value, we have extended our studies to samples from patients with pneumonia. We focused on the most promising enzyme-linked immunosorbent assays (ELISAs) (SeroCP and SeroCP Quant; Savyon) identified in our previous study and included a new ELISA (sELISA; Medac). The agreement betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 34 publications
1
14
0
4
Order By: Relevance
“…18,19 However, Hermann and colleagues reported that ELISAs that are fast and objective deliver seroprevalence results, sensitivities, and specificities that are very similar to those of the MIF test. 8 Our results corroborate other investigations that reported the presence of chlamydial structures and even viable C. pneumoniae in atherosclerotic plaques. Experimental proof, however, of an etiological role of C. pneumoniae in atherothrombosis has not yet been accomplished since a wellestablished animal model and a system of genetic recombination are not yet available.…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…18,19 However, Hermann and colleagues reported that ELISAs that are fast and objective deliver seroprevalence results, sensitivities, and specificities that are very similar to those of the MIF test. 8 Our results corroborate other investigations that reported the presence of chlamydial structures and even viable C. pneumoniae in atherosclerotic plaques. Experimental proof, however, of an etiological role of C. pneumoniae in atherothrombosis has not yet been accomplished since a wellestablished animal model and a system of genetic recombination are not yet available.…”
Section: Discussionsupporting
confidence: 95%
“…8 This test, based on specific C. pneumoniae peptides, is a semi-quantitative determination of specific IgG and IgA antibodies to C. pneumoniae. A result higher than 10 IU/mL was considered positive [9].…”
Section: Patientsmentioning
confidence: 99%
“…However, in a subsequent investigation by the same group, they reported that ELISA tests had high specificity and sensitivity and showed a good correlation with MIF tests in sera from patients with respiratory tract diseases and from control children. Antibody titers determined by quantitative ELISA also showed an acceptable correlation with those determined by MIF [60] .…”
Section: Elisamentioning
confidence: 78%
“…The common occurrence of C. pneumoniae infection is suggested by the high seroprevalence ($70%) observed in adults [2]. However, in recent studies [3][4][5], the prevalence of respiratory infections due to C. pneumoniae was reported to be much lower (,1.5%) than previously (6%-22%) [6].…”
mentioning
confidence: 97%